Enhancing Student-Student Online Interaction: Exploring the Study Buddy Peer Review Activity - Madland, Colin; Richards, Griff (International Review of Research in Open and Distributed Learning, 2016)
The study buddy is a learning strategy employed in a graduate distance course to promote informal peer reviewing of assignments before submission. This strategy promotes student-student interaction and helps break the social isolation of distance learning. Given the concern by Arum and Roksa (2011) that student-student interaction may be distracting from instead of contributing to academic achievement it was felt important to examine the way peer interaction can contribute to learning in a well-structured collaborative learning activity. This mixed-methods study (n=31) examined both quantitative and qualitative aspects of student perceptions of the study buddy activity. While quantitative findings regarding depth of processing were inconclusive due to the small and homogeneous sample, qualitative analysis showed very high levels of learner support for the activity as well as evidence that the activity encouraged learners to approach their learning with greater depth. 88% of study buddies said they found the activity well worth their time, and would recommend it for other graduate courses. It is thought with greater scaffolding, the quality of buddy feedback might be improved. The few who did not appreciate the activity felt let down by a lack of buddy commitment to the process.